(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The economic cost analysis of creating energy willow plantations in Ukraine is provided in the present paper. The experience of creating bioenergy willow plantations at scientific and industrial institutions in Ukraine has been used in the paper. The purpose of this scientific work is to conduct an analysis of the structure of cash expenses for the creation of bioenergy willow plantations based on the experience of various institutions of Ukraine. The analysis is based on a technological map created during the study on drained peat lands at Panfyly Research Station. Analyzing the cost structure by category, the data obtained during the creation of bioenergy willow plantations of Salix Energy LLC and the Institute of Bioenergy Crops and Sugar Beet were also taken into account. After analyzing all the technology stages of growing bioenergy willow, it was revealed that the most expensive is the second stage associated with the preparation for planting and planting willow cuttings in the context of the pricing policy in Ukraine. In general, more than 60% of all expenses fall upon the first year of cultivation. According to the experience of Ukrainian institutions, the cost structure will have a significant shift towards planting material - 55-60%. The remaining costs are distributed during the use of equipment in the field, which constitute 26-30% and transportation costs respectively are 12-19%.